Gender, sex and the postnational defense :militarism and peacekeeping - Kronsell, Annica (New York ; Oxford : Oxford University Press, 2012)
This text explores the post-national defense and its gender implications. It explores how the United Nations Security Council resolution to increase the participation of women in peace negotiations, humanitarian planning, peacekeeping operations,and governance has influenced the policy practices of the post-national defense.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Keywords: Women and war; Peacekeeping forces; Peace-building.; Women and peace; Militarism; Women and the military -- European Union countries; Sweden -- Armed Forces -- Women; Sweden -- Armed Forces -- Afghanistan